2018
DOI: 10.1007/s11356-018-2194-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption characteristics for heavy metals of active silicon adsorbent from leaching residue of lead-zinc tailings

Abstract: To comprehensively reuse the leaching residue obtained from lead-zinc tailings, an active silicon adsorbent (ASA) was prepared from leaching residue and studied as an adsorbent for copper(II), lead(II), zinc(II), and cadmium(II) in this paper. The ASA was prepared by roasting the leaching residue with either a NaCO/residue ratio of 0.6:1 at 700 °C for 1 h or a CaCO/residue ratio of 0.8:1 at 800 °C for 1 h. Under these conditions, the available SiO content of the ASA was more than 20%. The adsorption behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The disordering of silicate in Cu MS causes the overlap of the different absorption bands, which broaden the absorption band. Furthermore, the adsorption of the Cu would promote by the monosilicate [27].…”
Section: Discussionmentioning
confidence: 99%
“…The disordering of silicate in Cu MS causes the overlap of the different absorption bands, which broaden the absorption band. Furthermore, the adsorption of the Cu would promote by the monosilicate [27].…”
Section: Discussionmentioning
confidence: 99%
“…The newly developed Si-O stretching vibration peak at 589 cm −1 indicated that the SiO 2 network had been damaged [25]. The wide peak of the adsorbent at 1000-1100 cm −1 was attributed to the breaking of the mesh structure of quartz during heating to form disordered SiO 4 [14]. The tensile peak at 887 cm −1 was attributed to Si-O-Na [26].…”
Section: Characterization Of Ashmamentioning
confidence: 99%
“…Our team used leaching residue from lead-zinc tailings with high silicon content as a raw material to prepare an active silicate heavy metal adsorbent, which showed a very high adsorption capacity for the heavy metals Cu, Pb, Cd and Zn. The saturated adsorption capacities were 3.40, 2.83, 0.66 and 0.62 mmol/g, respectively [14].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Metals could be recycled from the tailings with separation and intensive leaching process. While, after metals recovery from Lead–Zinc Sulfide Tailings, a large amount of leaching residue of Lead–Zinc Sulfide Tailings (LRT) will be produced [ 1 ], and little attention has been paid to its disposal so far. The LRT output was varied based upon the different leaching recovery procedures [ 2 , 3 ], and its storage was stint by its acidity and the heavy metals.…”
Section: Introductionmentioning
confidence: 99%